(3SDGdGJ GHf CHj TjHI aj GdLQM hGdJYOjd Yf eTGjN ef GdHUQjjfs - (3Ydj Hf YHO Gddg Hf CHj TjHI GdeOjfjs ((3CHh HcQ Hf Ydi Hf ESeGYjd GdCfUGQi GdHgfSi GdTGaYi s)
(3ChdgG (B:s
(3CNHQfG CHh GdYHGS CMeO Hf YeQ Hf CfS GdYPQi HGdLRjQI hbQCg Ydjg s
(3BNQgG (B:s
(3bGd SeYJ YdjkG jbhd MQe Hf CHj MQe hCfG CSeY Yf ehSi Hf CYjf abGd cGf UGdMkG hSWG BNQ eG GfJgi Edjg Gdefbhd ef GdCUd gcPG ef GdSDGdGJ GdMeO ddg QH GdYGdejf s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3eUOQ GbJfGA GdCUd (B:s
(3CMeO GdKGdK (B(624 0 19)) s
Keywords: (3GdMOjK h GdeUWdMs